Standard study on the impact of integration in the multilateral ‎trading system: The experience of rising power in Latin America ‎‎(Brazil), "Lessons for the Algerian Economy‎‏"‏ - Tayeb Mazouzi; Hocine Medjaoui Trari (Dirassat Journal Economic Issue, 2016)
The purpose of this article is to recognize the reality of the experience of the State of Brazil in the field of trade liberalization in the multilateral trading system,  by measuring the impact of the opening of trade of this countries on economic growth rates and FDI flows during the period report (1980 - 2013). To achieve this goal, we used for this purpose the simultaneous integration test (cointegration) To know the long-term relationship between each of the opening of Trade and the Economic variables mentioned above. Not to mention that this research aims to find lessons from the Algerian economy as a state at the periphery of membership in the multilateral trading system.